Analyzing the Carbon Footprint of an Intravitreal Injection - Barry Power; Robert Brady; Paul Connell (Journal of Ophthalmic & Vision Research, 2021)
Abstract Purpose: To estimate the carbon footprint of a single intravitreal injection in a hospital-based intravitreal service. Methods: Greenhouse gas emissions attributable to the delivery of an intravitreal injection were calculated using a hybrid lifecycle analysis technique. Data were collected regarding procurement of materials, patient travel, and building energy use. Results: Carbon emissions associated with a single intravitreal injection, excluding the anti-VEGF agent, were 13.68 kg CO 2 eq. This equates to 82,100 kg CO 2 eq annually for our service. Patient travel accounted for the majority of emissions at 77%, with procurement accounting 19% for and building energy usage for 4% of total emissions. The omission of items considered dispensable from injection packs would reduce carbon emissions by an estimated 0.56 kg per injection – an annual saving of 3,360 kg CO 2 eq for our service. Similar savings, if extrapolated to a country the size of the United Kingdom, could yield annual carbon savings of 450,000 kg CO 2 eq. For context, a single one-way economy transatlantic flight produces 480 kg CO 2 eq per person. Conclusion: Wasteful practice in healthcare increases greenhouse gas production and drives climate change. The healthcare sector should be a leader in sustainable practice promotion and changes to high volume procedures have the largest impact on emissions. Long-acting agents offer the greatest future potential for meaningful reductions.